PROJECT ARTEMIS ACOUSTIC SOURCE - ACOUSTIC TEST PROCEDURE - Ferris, R. H.; Rollins, C. R. (1967)
Acoustic tests of the completed ARTEMIS acoustic source were conducted in Northwest Providence Channel in November 1965. A rigid 190 foot hydrophone boom pivoted at the base of the array structure enabled stable and accurate positioning of hydrophones at points in a vertical plane from 2.5 degrees above to 22.5 degrees below the acoustic axis of the source. The transfer function between the input to the amplifiers and the hydrophone output was measured over the frequency range from 300 to 500 hertz for two types of signals, continuous wave and pseudorandom sequences. Continuous wave measurements were made using conventional phase and amplitude measuring instrumentation whereas the measurements with pseudorandom sequences were performed with a cross-power spectrum analyzer. The cross-power spectrum analyzer was also used to obtain correlation functions between the signal input and acoustic output. Twenty transducer elements were instrumented with accelerometers and appropriate instrumentation was provided to permit monitoring of transducer element spring deflections, since the transducer springs are the critical factor limiting the allowable power input. This report includes a description of instrumentation, test procedures, and analysis of the methods employed.